2021
DOI: 10.2186/jpr.jpor_2019_581
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of new denture base material modified with gold  nanoparticles

Abstract: Purpose: Poly(methyl methacrylate) (PMMA) is the most commonly used material in the production of dental prostheses, and its application is often accompanied by the formation of biofilm. The aim of this work was the preparation of a PMMA/gold nanoparticles (AuNps) composite to improve the antimicrobial properties of heat-polymerised PMMA. The AuNPs were synthesised from gold (III) acetate by Ultrasonic Spray Pyrolysis (USP). In the present study, flexural strength and elastic modulus were investigated, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…In another study, nano-sized silver particles were reported to increase the thermal conductivity of the denture base resin and could be used in the palatal region of the prosthesis [41]. Similar results were found in another recent study using gold nanoparticles [42].…”
Section: Resultssupporting
confidence: 72%
“…In another study, nano-sized silver particles were reported to increase the thermal conductivity of the denture base resin and could be used in the palatal region of the prosthesis [41]. Similar results were found in another recent study using gold nanoparticles [42].…”
Section: Resultssupporting
confidence: 72%
“…Similar undesired changes in mechanical properties have also been observed with the use of nanoparticles, mainly due to particle agglomeration 29 . Although silanization is believed to improve homogeneity, a matrix-compatible micro-filler to improve the properties of acrylic-based denture resins has not been found 26 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these inorganic materials, zinc ions in particular have been explored as an alternative to conventional antimicrobials in dental materials 24,25 . The aforementioned additives have shown variable microbial resistance, often observed to increase with increasing concentration of additives [21][22][23]26,27 . However, the antimicrobial effects of the additives are mostly associated with compromised mechanical properties 23 .…”
mentioning
confidence: 99%
“…In the present study, dry AuNPs were used, which were synthesized by the USP method [ 43 ] and lyophilization for mixing into the PMMA matrix. The addition of AuNPs was also prepared with caution so as not to change the color of the PMMA, as we previously reported [ 44 ]. In this study, a decrease in biofilm formation on PMMA/AuNPs compared to conventional PMMA discs was demonstrated for the monomicrobial biofilms of C. albicans , E. coli , S. aureus and S. mitis .…”
Section: Discussionmentioning
confidence: 99%